2010
DOI: 10.5539/ijbm.v5n2p159
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reward and Recognition on Job Satisfaction and Motivation: An Empirical study from Pakistan

Abstract: Human resources are the most important among all the resources an organization owns. To retain efficient and experienced workforce in an organization is very crucial in overall performance of an organization. Motivated employees can help make an organization competitively more value added and profitable. The present study is an attempt to find out the major factors that motivate employees and it tells what is the relationship among reward, recognition and motivation while working within an organization. The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
248
1
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(283 citation statements)
references
References 10 publications
23
248
1
11
Order By: Relevance
“…Kube, Marechal, and Puppe (2006) confirmed that monetary incentives are effective during the shortterm period and noting the long-term period whereas non-monetary incentives givesignificant and consistent satisfaction. Danish and Usman (2010) opined that proper usage of rewards as a tool in an organization would produce a conducive environment so as the employees gets motivated and rise to the occasion. Lawler (1985) claimed that rewards leads to increased employees' satisfaction and will have a direct impact on employee's performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Kube, Marechal, and Puppe (2006) confirmed that monetary incentives are effective during the shortterm period and noting the long-term period whereas non-monetary incentives givesignificant and consistent satisfaction. Danish and Usman (2010) opined that proper usage of rewards as a tool in an organization would produce a conducive environment so as the employees gets motivated and rise to the occasion. Lawler (1985) claimed that rewards leads to increased employees' satisfaction and will have a direct impact on employee's performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Organizational rewards are known to help an organization boost the employees' motivation thus leading to employees' satisfaction. Danish and Usman (2010) stated that rewards system serve as the most contingent factor in keeping employees' self-esteem high and passionate.…”
Section: Introductionmentioning
confidence: 99%
“…A promotion program in an organization is a critical component for employees' encouragement, loyalty and satisfaction. (Teclemichael Tessema and Soeters 2006) , (Mustapha and Zakaria 2013), (Bhamani) and (Danish and Usman 2010) research results demonstrated that promotion practices have positive relationship with perceived performance of employees, and job satisfaction and employees' work motive respectively. Moreover, (Gaertner and Nollen 1989) and (Chughtai and Zafar 2006) results proved that promotion opportunities is positively related to employees commitment and they suggested that employees who have been promoted tends to be more committed.…”
Section: Promotionmentioning
confidence: 95%